Charting multidisciplinary research and action priorities towards the conservation and sustainable management of sea turtles in the Pacific Ocean a focus on Malaysia. - M. Ahmed, S. Wagiman, K. Ibrahim, S.C. Ho, H.C. Liew, B.H. Yeo, M.M. Lau, M.N. Basiron and D.S.K. Sharma (The World Fish Center, 2006)
Workshop Proceedings, 74